1983
DOI: 10.1128/jb.154.2.946-954.1983
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase secretion-negative mutant of Bacillus licheniformis 749/C

Abstract: An alkaline phosphatase secretion-blocked mutant of Bacillus licheniformis 749/C was isolated. This mutant had defects in the phoP and phoR regions of the chromosome. The selection procedure was based on the rationale that N-methyl-N'-nitro-N-nitrosoguanidine can induce mutations of closely linked multiple genes. The malate gene and the phoP and phoR genes are located at the 260-min position in the Bacillus subtilis chromosome; hence, the malate gene could be used as a marker for the mutation of the phoP and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Included among this third group of proteins are some where genetic analyses are beginning to shed light on the possible mechanisms of secretion. Perhaps the best characterised mutants are the Sec- [237] and sacU mutants of Bacillus sp. [220,226,268a].…”
Section: Other Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Included among this third group of proteins are some where genetic analyses are beginning to shed light on the possible mechanisms of secretion. Perhaps the best characterised mutants are the Sec- [237] and sacU mutants of Bacillus sp. [220,226,268a].…”
Section: Other Proteinsmentioning
confidence: 99%
“…[220,226,268a]. The Sec-mutants of B. licheniforrnis described by Kumar et al [237] have an additional electron-dense surface layer which is not found in wild-type cells, and accumulate alkaline phosphatase in discrete sites in the plasma membrane rather than releasing it into the medium. This may provide additional evidence for the existence of specific sites for protein export in the plasma membrane, as discussed in section 5.…”
Section: Other Proteinsmentioning
confidence: 99%
“…Bacillus licheniformis 749/C cells were grown in low-phosphate medium for alkaline phosphatase derepression. This medium contained 1% casein hydrolysate and 0.1% glucose (17). Growth continued for 4.5 h at 32°C with constant shaking.…”
Section: Methodsmentioning
confidence: 99%
“…Growth,: enzyme assay, and antibody production. B. licheniformis 749/C cells were grown in low-phosphate casein hydrolysate medium containing 0.1% glucose for 4.5 h at 32°C with constant shaking (15). Alkaline phosphatase activity was assayed by monitoring the release of p-nitrophenol from p-nitrophenyl phosphate as described previously (10); protein content was estimated by the method of Lowry et al (16).…”
Section: Methodsmentioning
confidence: 99%